2016
DOI: 10.1186/s40490-016-0080-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tools for differentiating Cyclaneusma minus morphotypes and assessing their distribution in Pinus radiata forests in New Zealand

Abstract: Background: Cyclaneusma needle cast (CNC) is a pine disease caused by the ascomycetous fungus Cyclaneusma minus (Butin) DiCosmo, Peredo and Minter. The pathogen occurs worldwide but is of particular significance in New Zealand where it infects Pinus radiata D. Don plantations. There are two morphological types of C. minus, termed C. minus 'simile' and C. minus 'verum', recently shown by multigene phylogenetic analysis to belong to distinct clades and therefore proposed to be two separate species. It is current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…A multigene phylogenetic analysis of New Zealand and Australian isolates of Cyclaneusma demonstrated that the separation of isolates by morphotype was consistent with genetic analysis and suggested the need for species descriptions to formally re-classify, as well as pathogenicity studies to understand phenotypic differences between the morphotypes (Prihatini et al, 2014). Hunter et al (2016) developed molecular tools for differentiating the 'verum' and 'simile' morphotypes and looked at their distribution throughout New Zealand. The study found that 'simile' was the most common morphotype in New Zealand, and that molecular classification was much more accurate than morphological assessments.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…A multigene phylogenetic analysis of New Zealand and Australian isolates of Cyclaneusma demonstrated that the separation of isolates by morphotype was consistent with genetic analysis and suggested the need for species descriptions to formally re-classify, as well as pathogenicity studies to understand phenotypic differences between the morphotypes (Prihatini et al, 2014). Hunter et al (2016) developed molecular tools for differentiating the 'verum' and 'simile' morphotypes and looked at their distribution throughout New Zealand. The study found that 'simile' was the most common morphotype in New Zealand, and that molecular classification was much more accurate than morphological assessments.…”
Section: Introductionmentioning
confidence: 85%
“…At first, differences in ascospore length and characteristics of the fungus grown on agar plates indicated that there were two morphological types of C. minus in New Zealand, termed C. minus 'simile' and C. minus 'verum' (Dick et al, 2001). However, with the development of molecular tools to differentiate these morphotypes, another morphotype was suggested to be present in the New Zealand C. minus population (Hunter et al, 2016). Host genotype is known to strongly influence symptom expression of CNC (Ismael et al, 2020;Suontama et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lack of long-term forest health data, local selection pressures may have shaped changes in the D. septosporum population after its arrival in New Zealand. Pine needles are a biotically rich environment, containing diverse endophytes and latent pathogens that are potential competitors [65,66]. Co-infection with different communities of commensal, mutualistic, or parasitic microorganisms can promote or temper the evolution of virulence [67,68] and these communities are likely to be different in a new environment, such as New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogenous fertiliser applications increase P. radiata productivity in low fertility soils (Mead & Gadgil 1978;Mead et al 1984;Hunter et al 1986;West et al 1988). However, the mean annual rate of N fertiliser use across the New Zealand planted estate is 8 kg ha -1 , which is low compared to other sectors (Matson 2019).…”
Section: Introductionmentioning
confidence: 99%